2017
DOI: 10.1371/journal.pone.0175574
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of EBV seroprevalence and primary infection age in a French hospital and a city laboratory network, 2000–2016

Abstract: BackgroundAccording to rare studies, the age at EBV primary infection (PI) has recently risen in some developed countries. A later age at infection is generally considered a risk factor for severe EBV PI, although few studies exist on this subject. Our investigation aimed to determine whether EBV seroprevalence and EBV PI epidemiology have evolved in France, and to what extent age and infection intensity (regarding biological parameters) are correlated.Methods and findingsWe conducted a retrospective study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
39
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 25 publications
12
39
1
5
Order By: Relevance
“…Seroepidemiologic studies are also compatible with the findings in the present study, with reported high seroprevalence (80%‐90%) in immunocompetent adults, and lower seroprevalence in children . It has, however, to be noted that data on EBV prevalence in the general population are relatively rare, and a change in EBV epidemiology has been reported over the last decades in high‐income countries with decreasing overall EBV prevalence and increasing age of primary infection . The relatively high prevalence in tonsils is coherent with the fact that EBV is known to infect the intraepithelial B cells of the tonsils where it may establish latent infection .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Seroepidemiologic studies are also compatible with the findings in the present study, with reported high seroprevalence (80%‐90%) in immunocompetent adults, and lower seroprevalence in children . It has, however, to be noted that data on EBV prevalence in the general population are relatively rare, and a change in EBV epidemiology has been reported over the last decades in high‐income countries with decreasing overall EBV prevalence and increasing age of primary infection . The relatively high prevalence in tonsils is coherent with the fact that EBV is known to infect the intraepithelial B cells of the tonsils where it may establish latent infection .…”
Section: Discussionsupporting
confidence: 91%
“…14,45 It has, however, to be noted that data on EBV prevalence in the general population are relatively rare, and a change in EBV epidemiology has been reported over the last decades in high-income countries with decreasing overall EBV prevalence and increasing age of primary infection. 18,[44][45][46] The relatively high prevalence in tonsils is coherent with the fact that EBV is known to infect the intraepithelial B cells of the tonsils where it may establish latent infection. 2,47 Indeed, one specificity of the tonsil brushing protocol used is the high amount of retrieved lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
“…This raises the possibility of geographic, ethnic or genetic differences that impact the risk of post‐transplant EBV‐SMT, but this remains speculative at this time. The seroprevalence of EBV in children and adults and the age‐specific risk of primary EBV infection in our transplant population is similar to that reported in the general population of the United States and Western Europe . In contrast Asian populations appear to acquire EBV earlier and more frequently in childhood and appear to have an increased susceptibility to a number of EBV‐associated malignancies .…”
Section: Discussionsupporting
confidence: 81%
“…Chabay and Preciado (2013) reported that the anti-VCA IgG prevalence among children less than 15 years of age in Argentina was 72% [10]. Similar results were also found in most previous studies [8] [11] [12]. Epstein-Barr virus infection is very common in the United States since more than 90% of adults are antibody positive by the age of 35 years.…”
Section: Introductionsupporting
confidence: 71%